The Influence of Corruption Control, Financial Reporting Quality, and Local Own-Source Revenue on Achieving SDG 1 - Mimin Alga Firdiansyah; Andi Chairil Furqan; Femilia Zahra; Muhammad Ikbal Abdullah (Owner : Riset dan Jurnal Akuntansi, 2025)
Access to basic sanitation services represents a critical component in the achievement of the Sustainable Development Goals (SDGs), particularly Target 1.4.1, which emphasizes the necessity of providing essential services to all segments of the population without discrimination. Although national statistics indicate a gradual improvement in access, significant disparities persist at the subnational level, highlighting challenges in local fiscal governance. This study aims to analyze the simultaneous influence of Corruption Control (CC, measured using the Corruption Control Effectiveness Index (CCEI), Financial Report Quality (QFR, measured through audit opinions), and Local Own-Source Revenue (LOSR) on access to basic sanitation services. Employing a quantitative approach through a multiple linear regression model, this research utilizes panel data from 495 local governments across Indonesia over the period 2021–2022. The empirical results reveal that all three independent variables CC, QFR, and (LOSR) exert a positive and statistically significant effect on the expansion of sanitation service coverage. These findings underscore the relevance of the good governance framework in the context of public financial management at the local level. The study concludes that strengthening fiscal integrity, enhancing financial transparency, and promoting fiscal autonomy are key strategies to accelerate equitable and sustainable access to sanitation services. Furthermore, the results suggest that improvements in local institutional quality and capacity can play a vital role in advancing inclusive development. Future research is recommended to incorporate additional indicators under SDG Target 1.4.1, such as access to safe drinking water, adequate housing, and productive assets, to generate a more comprehensive understanding of local development dynamics.